Calculati:
[(-3^4)*(-3)^4*(-3)^30+(-3)^38+(-7)^124:(-7)^55+(7^3)^23-4*8]*45^0
Răspunsuri la întrebare
Răspuns de
2
[(-3^4)*(-3)^4*(-3)^30+(-3)^38+(-7)^124:(-7)^55+(7^3)^23-4*8]*45^0=
=[(-3^4)*(+3)^4*(+3)^30+(+3)^38+(+7)^124:(-7)^55+(7^69)-32]*1=
=[(-3^38)+(+3)^38+(-7)^69+7^69-32]*1=
=(0+0-32)*1=-32
=[(-3^4)*(+3)^4*(+3)^30+(+3)^38+(+7)^124:(-7)^55+(7^69)-32]*1=
=[(-3^38)+(+3)^38+(-7)^69+7^69-32]*1=
=(0+0-32)*1=-32
biutza98765:
Multumesc din suflet!
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Istorie,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă